2015
DOI: 10.1021/acs.jmedchem.5b00586
|View full text |Cite
|
Sign up to set email alerts
|

New Frontiers in Druggability

Abstract: A powerful early approach to evaluating the druggability of proteins involved determining the hit rate in NMR-based screening of a library of small compounds. Here we show that a computational analog of this method, based on mapping proteins using small molecules as probes, can reliably reproduce druggability results from NMR-based screening, and can provide a more meaningful assessment in cases where the two approaches disagree. We apply the method to a large set of proteins. The results show that, because th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
162
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(169 citation statements)
references
References 168 publications
7
162
0
Order By: Relevance
“…[23, 25, 36–38]. In particular, we have previously established that, when using 16 probes types for the mapping, the sites that are known to be druggable invariably contain a strong hot spot containing 16 or more probe clusters [24, 39]. Second, since the primary hot spot is the location with the highest binding potency for small molecules, we expect that fragment hits are most likely to bind at this site.…”
Section: Hot Spots and Fbddmentioning
confidence: 99%
See 3 more Smart Citations
“…[23, 25, 36–38]. In particular, we have previously established that, when using 16 probes types for the mapping, the sites that are known to be druggable invariably contain a strong hot spot containing 16 or more probe clusters [24, 39]. Second, since the primary hot spot is the location with the highest binding potency for small molecules, we expect that fragment hits are most likely to bind at this site.…”
Section: Hot Spots and Fbddmentioning
confidence: 99%
“…Targets that lack a primary hot spot of sufficient strength are not suitable for FBDD, and have poor overall prospects for inhibitor development by any means [21, 27]. The FTMap analysis used to derive these results was based on mapping the ligand-free proteins, allowing druggability to be assessed for any target that has been crystallized even before investing time or resources into lead discovery [39]. Whether a bound fragment will have a robust binding mode also depends largely on CC1.…”
Section: Hot Spots and Fbddmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Foss et al have demonstrated that small molecules which disrupt bacterial membrane function (such as cinnamaldehye, totarol and sanguinarine) produce similar phenotypes to FtsZ inhibitors. [60] The druggability of regions of this protein is also a matter for debate; Kozakov et al have used the FTMap algorithm [61] to characterize the ligand-binding hot spots of the ZipA/FtsZ protein-protein interaction and concluded that this interface is not a druggable target [62].…”
Section: Ftsz Inhibitorsmentioning
confidence: 99%